2019
DOI: 10.1007/s10658-019-01786-z
|View full text |Cite
|
Sign up to set email alerts
|

Fast and reliable screening assay developed to preselect candidate Soft Rot Pectobacteriaceae Tn5 mutants showing resistance to bacteriophage infection

Abstract: We present a simple, fast and inexpensive screening assay to preselect candidate Pectobacterium spp. and Dickeya spp. Tn5 mutants, which carry transposon insertions in genes putatively encoding proteins used by lytic bacteriophages to interact with host cells, for the follow-up studies. The proposed method is fast and costeffective and it does not need any specialized laboratory equipment and/or technical support. The Tn5 mutants are generated using random transposon mutagenesis with the mini-Tn5 transposon. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Like other studies [ 24 , 49 ], this study demonstrated that the resazurin microplate method is faster and as accurate as the colony-count technique and is more precise and has a lower minimum detection limit than the OD method. As such, this fluorometric method is a good alternative to monitor the concentration of different bacteria during their inactivation by several phages at the same time and, consequently, is a promising technique to screen and preselect new or known phages by their inactivation profile.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Like other studies [ 24 , 49 ], this study demonstrated that the resazurin microplate method is faster and as accurate as the colony-count technique and is more precise and has a lower minimum detection limit than the OD method. As such, this fluorometric method is a good alternative to monitor the concentration of different bacteria during their inactivation by several phages at the same time and, consequently, is a promising technique to screen and preselect new or known phages by their inactivation profile.…”
Section: Discussionsupporting
confidence: 76%
“…Other colorimetric methods were successfully used in phage screening [ 22 , 49 , 50 , 51 , 52 , 53 ]. Some authors used the tetrazolium-based assay to screen 98 single Acinetobacter baumannii -specific lytic phages to inactivate A. baumannii [ 22 ], others used the resazurin assay to assess the cell activity of Pectobacterium atrosepticum with CRISPR-Cas immunity upon infection with the virulent phages [ 52 ], others used the resazurin assay as a fast screening assay to preselect Dickeya solani and Pectobacterium parmentieri Tn5 mutants in genes coding for proteins used by lytic phages φD5 and φA38 as receptors [ 49 ] and others used the resazurin assay to detect for the presence of phages specific to Streptococcus diacetilactis in cottage cheese samples [ 61 ]. However, these studies only tested the phages’ ability to inactivate or not inactivate the targeted bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phage-resistant P. parmentieri Tn5 mutants were preselected as previously described [ 73 ]. To validate their bacteriophage resistance, each Tn5 mutant exhibiting a ϕA38-resistant phenotype in the initial screen was subjected to repeatable phage challenge assays and plaque formation assays as previously described [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 Host challenge assay of the parental (D. solani IPO2222) strain (marked) and the selected bacteriophage-resistant IPO2222 Tn5 mutants in the absence and presence (+ phiD5) of lytic bacteriophage ϕD5. Per mutant to be analyzed, as described earlier (Czajkowski et al 2019), in duplicates, the wells of the 96-wells plate were inoculated with 50 µl of freshly prepared bacterial cultures (IPO2222 wild type or IPO2222 Tn5 mutants) in LB broth (final cfu ml − 1 of 5 × 10 4 ). Subsequently, 200 µl of bacteriophage ϕD5 suspension in LB broth was added per well (final pfu ml − 1 of 2 × 10 7 ).…”
mentioning
confidence: 99%